Relación entre los hogares con acceso a internet y la actividad económica de telecomunicaciones y otros servicios de información de Loreto periodo 2017 – 2021 - Starke Rojas, Manuel Fernando (2024)
The internet has become a mandatory tool in the population's different activities, reducing distances, bringing people closer together and expanding markets, but not all regions of the country have good service. The objective of this master's thesis is to determine the relationship between homes with internet access and the economic activity of Telecommunications and Other Information Services in Loreto, in the period 2017 - 2021. Pursuing this purpose, the Quantitative research is carried out, Correlational level and Non-Experimental design. The main conclusion shows that Loreto homes that have internet are directly related to the economic activity of Telecommunications and Other Information Services in the period 2017 - 2021, validated through the Correlation Coefficient which was r = 0.965986657; and the Coefficient of Determination that reached R2 = 0.933130222. Likewise, Loreto has the Amazonian population aged 6 and over who use the internet the most, with an average of 917,218 people, representing 35.95% of the total. The highest frequency of use corresponds to Once a Day with 1,809,009 individuals, which is equivalent to 70.89% of the total, highlighting the importance of the Internet in the development of the daily activities of the Amazonian population. The economic activity of Telecommunications and Other Information Services is 3.87% of the GVA.